Mapping; Ranah Affektif (Sikap) Wirausaha Mahasiswa Politeknik Swasta di Palembang - Eni Cahyani; Mugi Harsono (Jurnal Ilmiah Ekonomi Global Masa Kini)
This research is a descriptive study, which aims to investigate the entrepreneurial character of early-level students at the Private Polytechnic in Palembang. The method used to collect data was a sample aiming with the snowball technique. Respondents involved in this study were 203 respondents to fill in 18 questions in the questionnaire. Data analysis using descriptive statistical methods, determined the rank in each character with a comparison between the actual score and the ideal score. The results of this study indicate that of the 6 (six) entrepreneurial characters the calculation of the ideal ideal score is 50.65 (high). Where 4 (four) dominant characters, namely self-confidence, task and result-oriented, originality and future-oriented, while the other 2 (two) entrepreneurs, namely leadership and risk-taking, get a score criterion of 44.1% (moderate). The implication of this research is to provide information for the mapping of the entrepreneurship course curriculum providing information for practical and theoretical material that is in the semester learning plan. Keywords: Character, entrepreneurship, students